Identity Crisis and Religious Conversion: The Religious Dynamics of Modern Society - Safitri, Aulia; Hady Ningsih, Salsabila; Surawan, Surawan (Universitas Muhammadiyah Yogyakarta, 2025)
This study investigates the factors influencing young Muslims' decisions to leave Islam, utilizing a qualitative approach and digital ethnography methods. TikTok, as a prominent platform for youth expression, serves as the research focus. Data were gathered through non-participatory observation of relevant content and analyzed using thematic analysis. Three primary themes emerged: Faith Struggles, Environmental Influences, and Interpersonal Relationships. Faith struggles arise from internal conflicts between religious values and personal life experiences, including mismatches between faith and identity. Environmental influences stem from exposure to diverse cultures and religions, fostering emotional attachments. Interpersonal relationships, particularly interfaith marriages, significantly contribute to conversion decisions. The findings underscore TikTok's role as a platform for identity exploration among youth, offering valuable insights for religious communities to address spiritual needs amidst modernity and identity crises.